EMPODERAMENTO FEMININO: TERRITÓRIOS DA CIDADANIA NAS ELEIÇÕES DE 2008 E 2012 - Chimin Junior, Alides Baptista (2016)
This study pursued the answer to the following central question: “How the effect of women empowerment policies promoted by the federal program of Territórios da Cidadania occurs on female representation in the 2008 elections and 2012?". The federal program Territories of Citizenship, Federal Decree 11,503 / 2008, has as its main goal, to promote economic development and to universalize basic citizenship programs. One of its most important pillars to achieve this goal is to produce actions to overcome gender inequalities. This federal program is organized on scale form because it has as performance basis a set of municipalities that have similarities on economic and environmental characteristics, cultural identity commonalities and social cohesion. On this sense, the research will focus its analysis on the municipal elections, especially in election financing networks and proportional gender representation of councilors chambers seeking to compare the electoral pleas of 2008 and 2012 to analyze the effectiveness of policies implemented there. For this, we used elections data available on TSE website structured on electoral database. The database was set up on network donations of both claims and the resulted statistics analysis highlighted the evidence of a change, occurred in these municipalities on both elections. The research undertaken shows that the position of women in electoral financing networks is essential for the achievement of success on the conquest of places in the municipal legislature. The central position in investments have been achieved by women who already have family translation in the political field as well as a wide sociability in local institutions, thus becoming, targets lenders. However, the great mass of women candidates, have a low profile on professional and educational qualifications, and little chance of attracting financial partnerships, hurting their chances of electoral success.